2014
DOI: 10.1002/jpln.201300610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic and other management practices on soil nematode communities in tea plantation: a case study in southern China

Abstract: Four major tea management practices (organic, pollution-free, conventional, and semi-natural) are employed in Chinese tea plantations at present. These practices can induce changes in the physiochemical parameters, microorganism community and enzyme activity in tea plantation soil. However, understanding of their effects on soil nematodes is still scarce. This study aimed to investigate whether and how different management practices affect the biodiversity, function, and structure of soil nematode communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 34 publications
2
15
1
Order By: Relevance
“…Combined with the ecological indices BI, which is related to soil properties and decomposition pathways 24 , we found that higher CI value for the three straw mulching treatments appeared in the whole-plot coverage treatments ( all n ). Our results contrast with those of other studies, which found that bacterial-dominated decomposition pathways were the most common pathways 20 . This discrepancy could be explained mainly by the observed variations in the abundances of bacterivores and fungivores among the different coverage distances.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Combined with the ecological indices BI, which is related to soil properties and decomposition pathways 24 , we found that higher CI value for the three straw mulching treatments appeared in the whole-plot coverage treatments ( all n ). Our results contrast with those of other studies, which found that bacterial-dominated decomposition pathways were the most common pathways 20 . This discrepancy could be explained mainly by the observed variations in the abundances of bacterivores and fungivores among the different coverage distances.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, this finding is also contrary to our first hypothesis that different straw mulching treatments would increase the number of soil nematodes. The reasons are as follows: on the one hand, phenolic acids enter the soil through the secretions of walnut roots and the decomposition of a large amount of straw residues, which results in an increase in phenolic acids in the soil and a decrease in the total number of soil nematodes and other nematodes 20 . On the other hand, straw mulching returns pathogenic bacteria and parasite eggs to the field directly.…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain high yield and high quality of vegetable, farmers usually applied abundant organic and N fertilizer to greenhouse filed. However, high input of nutrition were not fully utilized by soil microorganisms and plants, the extra nutrition remained in the soil, thus lead to a series of soil problems such as soil degradation, salt accumulation and pH declining in greenhouse with long planting history [13,49-51]. A general conclusion that N fertilization caused the soil pH decreased while EC increased significantly, indicating that long-term inorganic N fertilization causes soil acidification and salinization [13,52-54].…”
Section: Discussionmentioning
confidence: 99%
“…However, high input of nutrition were not fully utilized by soil microorganisms and plants, the extra nutrition remained in the soil, thus lead to a series of soil problems such as soil degradation, salt accumulation and pH declining in greenhouse with long planting history [13,49-51]. A general conclusion that N fertilization caused the soil pH decreased while EC increased significantly, indicating that long-term inorganic N fertilization causes soil acidification and salinization [13,52-54]. The pH decrease may be resulted from the production of acidic metabolites came from the process of urea assimilation by soil microorganisms [55] and from the process of nitrification [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation